Adoption of Mobile Learning: Education’s Use of App-Based Learning Management Systems & Ethical Implementation - Sabbar Dahham Sabbar; Abdul Rahman Kadir; Mursalim Nohong; Arifuddin Mannan; Omer Mohamed Taha Alkanan; Sulaiman Abd Anter (International Journal of Interactive Mobile Technologies (iJIM), 2025)
This study examines the adoption of mobile learning (M-learning) through app-based learning management systems (LMS) in higher education, aiming to identify key factors influencing students’ usage behavior and continuing adoption intentions. Using an integrated theoretical framework combining the unified theory of acceptance and use of technology (UTAUT) and the expectation-confirmation model (ECM), the research employs a quantitative, cross-sectional design. Data were collected from 399 university students with M-learning experience, using a structured online questionnaire distributed via institutional portals and academic social media channels. Partial least squares structural equation modeling (PLS-SEM) was used to analyze the data and test direct and mediating effects among key variables. The findings reveal that performance expectancy and satisfaction are the strongest predictors of M-learning adoption, while interface design quality and facilitating conditions play significant but secondary roles. The study confirms satisfaction as a critical mediator between initial expectations and long-term usage intentions, highlighting its central role in sustaining engagement with M-learning platforms. These results contribute to educational technology literature by validating an integrated adoption model specifically for app-based LMS and providing empirical evidence on the hierarchical importance of different adoption factors. Practical implications suggest that educational institutions should prioritize user experience design and performance-related functionalities when implementing M-learning solutions, while also ensuring reliable technical support.